Efecto de la inserción laboral en la calidad de vida de las madres usuarias del programa del complejo asistencial de menores "josefina pinillos de larco". trujillo, año 2013 - Morales Fasanando, Cinthia Luz (2014)
In this descriptive study, whose approach is quantitative - qualitative, was inves-tigated on the "Effect of employment on the quality of life of users mothers Child Care Complex" and how this positively affects both. It was used as data collection instrument guide observation, interview and Scale Olson & Barnes, managing to organize the necessary information. And then the analysis is passed to verify and discuss loin descriptive study, Whose approach is quantitative - qualitative, was Investigated on the "Impact of employment in the quality of life for families of users mothers Child Care Com-plex" and how positively Affects both. It was used as data collection instrument guide observation, interview and Scale Olson & Barnes, managing to organize the Necessary information. And Then the analysis was passed to verify and discuss the results with charts and graphs illustrating comparatively sustaining them, framed the theoretical foundations and organized data information. The primary objective was to describe and Explain the employment of mothers in the quality of life of Their Families, having Given and received as an Im-portant That result the labor market has a positive impact on them, as well per-sonally Manages to acquire more autonomy and management of Their family life. In This present work is not worth Mentioning That single mothers manage to meet your goals and expectations, When They Have support, be public or per-sons These Institutions That motivate them to Improve Their quality of life and of the members That Make His familys results illustrating with charts and graphs comparatively sustaining them, framed the theoretical foundations and orga-nized information data. The primary objective was to describe and explain the employment of mothers in the quality of life of their families, having given and received as an important result that the labor market has a positive impact on them, as well personally manages to acquire more autonomy and management of their family life. In this present work is not worth mentioning that single mothers manage to meet your goals and expectations, when they have support, be these public or persons institutions that motivate them to improve their quality of life and of the members that make his family.